Swift vs. Objective-C: A New Programming Language - Garcia, Cristian Gonzalez; Espada, Jordan Pascual; G.-Bustelo, B. Cristina Pelayo; Lovelle, Juan Manuel Cueva (International journal of interactive multimedia and artificial intelligence, 2015)
The appearance of a new programming language gives the necessity to contrast its contribution with the existing programming languages to evaluate the novelties and improvements that the new programming language offers for developers. These kind of studies can show us the efficiency, improvements and useful or uselessness of the new programming languages. Also these studies can show us the good or bad properties of the existing programming languages. For these reasons, these studies allow us to know if the new programming language is offering improvements or relapses. In this article, we compare the new programming language of Apple, Swift, with the main programming language of Apple before Swift, Objective-C. We are going to show the differences, characteristics and novelties to verify the words of Apple about Swift. With that we want to answer the next question: Is Swift a new programming language easier, more secure and quicker to develop than Objective-C? Keywords--Object oriented programming, Programming, Functional programming, Programming profession, Software